2012
DOI: 10.1007/s00018-012-1013-6
|View full text |Cite
|
Sign up to set email alerts
|

NOX enzymes: potential target for the treatment of acute lung injury

Abstract: Acute lung injury (ALI) and its more severe form, acute respiratory distress syndrome (ARDS), is characterized by acute inflammation, disruption of the alveolarcapillary barrier, and in the organizing stage by alveolar pneumocytes hyperplasia and extensive lung fibrosis. The cellular and molecular mechanisms leading to the development of ALI/ARDS are not completely understood, but there is evidence that reactive oxygen species (ROS) generated by inflammatory cells as well as epithelial and endothelial cells ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 125 publications
2
44
0
Order By: Relevance
“…Pulmonary endothelial activation has been shown to be a critical event in the pathogenesis of sepsis-induced lung injury in animal models and can contribute to the vascular injury and remodeling seen in BPD (23,35). Pharmacological modulation of Nox activity may find use as adjunct therapy to limit lung injury and vascular remodeling in BPD (9).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary endothelial activation has been shown to be a critical event in the pathogenesis of sepsis-induced lung injury in animal models and can contribute to the vascular injury and remodeling seen in BPD (23,35). Pharmacological modulation of Nox activity may find use as adjunct therapy to limit lung injury and vascular remodeling in BPD (9).…”
Section: Discussionmentioning
confidence: 99%
“…The NOX2 system and other NOX enzymes have been implicated in ALI/ARDS in several studies. NOX2 and other NOX isoforms are expressed in endothelial and epithelial cells of the lung, where they may participate in early signaling events preceding ALI/ARDS (39,298). Neutrophil infiltration into the alveolar spaces of the lung during the acute phase of ALI/ARDs is clearly visible in postmortem lung sections from ARDS patients as well as in bronchoalveolar lavage fluid (181).…”
Section: Nox2 As a Target For Drug Developmentmentioning
confidence: 99%
“…Although we showed that mouse lung endothelial cells express increased Ang2 and Tie2 after systemic LPS, the rest of our data were obtained in primary cells in vitro, and, therefore, verification of the results of this study in animal models expressing angiogenic factors in a tissue-restricted manner will enable us to better understand the significance of these findings. This assumes translational significance because inhibiting Ang2 using antibodies or modulating Nox2 activity are emerging as promising strategies to decrease lung injury in bacterial sepsis (51,52).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%